Impacts of agricultural intensification on farmland birds and risk assessment of pesticide seed treatments - Brodeur, Celine Marie; Poliserpi, Maria Belen (Royal Society of Chemistry, 2023)
Agriculture is nowadays the largest driver of global environmental change, modern agricultural systems being a primary cause of biodiversity loss, including bird declines. Agricultural intensification affects bird populations through both a reduction in landscape heterogeneity and an increase in the use of pesticides, which negatively influences a variety of bird species. The objective of this chapter is to examine how agricultural intensification and the associated increase in pesticide use can affect farmland birds. Special attention is given to the case of pesticide-treated seeds, and the current guidelines on how to perfom the risk assessment of seed treatments are explained. Nevertheless, because a number of registered pesticide seed treatments have been found to pose a risk to farmland birds, current regulatory risk assessment protocols need to be improved so as to provide more accurate predictions of real-life situations and to better protect bird populations.